PERKEMBANGAN KOGNITIF ANAK MELALUI PERMAINAN PUZZLE DI TK KRISTEN REHOBOTH KECAMATAN NUSANIWE KOTA AMBON - Ludia Anika Demny; L.J .Lokollo; Lisa M. Sahetapy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze and determine the improvement of children's cognitive development through puzzle games at Rehoboth Christian Kindergarten, Ambon. The research was motivated by the importance of cognitive stimulation during the golden age, where initial observations indicated suboptimal utilization of puzzle media for children aged 5-6 years. Teachers' methods lacked variety and children struggled with game instructions. Using Classroom Action Research based on Kemmis and McTaggart's model, the study was conducted in two cycles with 16 children from Group B (aged 5-6 years). Each cycle included planning, action, observation, and reflection stages. Data collection employed participatory observation, teacher interviews, and documentation analysis. Results showed progressive improvement: only 15% of children reached "Very Good Development" (BSB) category in pre-cycle; this increased to 26.5% after Cycle I; and surged to 66.7% at the end of Cycle II. The findings conclude that planned and interactive implementation of puzzle games (numbers, geometry, fruits, and animals) is highly effective in enhancing children's cognitive development at this kindergarten.